A dual responsive photonic liquid for independent modulation of color brightness and hue. Issue 7 (21st May 2021) - Liu, Yun; Fan, Qingsong; Zhu, Guanghao; Shi, Gongpu; Ma, Huiru; Li, Wei; Wu, Tianlong; Chen, Jitao; Yin, Yadong; Guan, Jianguo
Abstract : The brightness and hue of structural colors can be independently, continuously, and reversibly tuned in an aqueous suspension containing Fe3 O4 @poly( N -isopropyl acrylamide) flexible photonic nanochains by changing the magnetic field and temperature. Abstract : Responsive chromic materials are highly desirable in the fields of displays, anti-counterfeiting, and camouflage, but their advanced applications are usually limited by the unrealized delicate and independent tunability of their three intrinsic attributes of color. This work achieves the separate, continuous, and reversible modulation of structural color brightness and hue with an aqueous suspension of dual-responsive Fe3 O4 @polyvinylpyrrolidone (PVP)@poly( N -isopropyl acrylamide) (PNIPAM) flexible photonic nanochains. The underlying modulation mechanism of color brightness was experimentally and numerically deciphered by analyzing the morphological responses to stimuli. When an increasing magnetic field was applied, the random worm-like flexible photonic nanochains gradually orientated along the field direction, due to the dominant magnetic dipole interaction over the thermal motion, lengthening the orientation segment length up to the whole of the nanochains. Consequently, the suspension displays increased color brightness (characterized by diffraction intensity). Meanwhile, the color hue (characterized by diffraction frequency) could be controlled by temperature, due to the volume changes of the interparticle PNIPAM. The achieved diverse color modulation advances the next-generation responsive chromic materials and enriches the basic understanding of the color tuning mechanisms. With versatile and facile color tunability and shape patterning, the developed responsive chromic liquid promises to have attractive potential in full-color displays and in adaptive camouflages.